Non-cash payment method using QR codes in an automated microcontroller-based vending machine - Rahman, Md. Shahidur; Bintu, Shamiha Yeasin; Aman, Sidratul (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.